PULMONARY AND INTRACRANIAL RADIOGRAPHIC PRESENTATIONS OF LANGERHANS CELL HISTIOCYTOSIS - Mohammed, D.; Patel, S. B. (International Journal of Medicine and Medical Research, 2019)
Background. Langerhans Cell Histiocytosis is a rare disease that affects 1 to 2 adults per million worldwide and often consists of systemic manifestations including pulmonary, intracranial and osteolytic lesions and endocrinologic abnormalities such as Diabetes Insipidus. Objective. The objective of this case report was to expand the medical literature of this rare disease. Methods. A case report of a 51-year-old female patient presenting with systemic symptoms as a result of Langerhans Cell Histiocytosis is presented. Results. A 51-year-old female presented with epistaxis, fatigue, polydipsia, polyuria, headaches and dyspnea. After initial x-rays showed multiple lung and liver nodules and the patient suffered subsequently from a unilateral pneumothorax, an open lung biopsy was recommended. On a pathological basis, the patient was diagnosed with Langerhans Cell Histiocytosis. This report focuses on the radiological presentations of the manifestations of Langerhans Cell Histiocytosis, particularly the presentations in the lung and intracranial regions. Conclusions. Langerhans Cell Histiocytosis is an incredibly rare disease that presents systemically. Recognizing and differentiating radiographic presentation of these patients is important to determine the need for confirmation by biopsy and early chemotherapeutic intervention.